STUDY ON ARTS, CRAFTS AND DANCES OF THE GOND COMMUNITY OF NUAPADA DISTRICT IN ODISHA - Majhi, Hutasan; Mohapatra, R. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The arts, crafts and dances of the people of Gond community of the Nuapada district are the significant aspects of the tribal cultural heritage of Odisha in India. This study is focusing on the rich cultural heritage of the Gonds residing in the Nuapada district of western Odisha particularly their art, paintings, craft, and dances. The Gond tribe people is known for decorating the exterior walls of their houses with intricate artwork believed to bring respectable providence. The research aimed to assess the knowledge of Gond art among the community near the Boden block of Nuapada district of Odisha, focusing on themes monogram patterns, designs, motifs, colours, media used, and institutions involved of the promotion of this art custom. The Maadli and Dalkhaiand Ghumura dances in particular are highlighted as a significant cultural expression among the Gond community of the Kalahandi and Nuapada districts, performed in honour of the deity Budha Deo through dance and song. The study emphasizes the urgent need for the preservation and documentation of the Maadli dance, which is on the verge of extinction of the Nuapada district. The Gond tribe of Nuapada is one of the major tribal communities of Odisha as well as Central India. The name “Gond” is derived from “Kond,” meaning green mountains of the Dravidian idiom of the Gond tribe. The painting is a popular folk art of the Gond tribe/ community of the Nuapada district of Odisha. The cultural heritage in the form of arts, crafts, songs and dances of Gond community is very interesting study for scholars as well as historians. So, the authors have taken modest venture to focus on the arts, crafts and dances of the Gonds of the Nuapada District in Odisha.